Size conservation emerges spontaneously in biomolecular condensates formed by scaffolds and surfactant clients - Sanchez-Burgos, Ignacio; Joseph, Jerelle A.; Collepardo-Guevara, Rosana; Espinosa, Jorge R. (Nature Publishing Group UK, 2021)
Abstract: Biomolecular condensates are liquid-like membraneless compartments that contribute to the spatiotemporal organization of proteins, RNA, and other biomolecules inside cells. Some membraneless compartments, such as nucleoli, are dispersed as different condensates that do not grow beyond a certain size, or do not present coalescence over time. In this work, using a minimal protein model, we show that phase separation of binary mixtures of scaffolds and low-valency clients that can act as surfactants—i.e., that significantly reduce the droplet surface tension—can yield either a single drop or multiple droplets that conserve their sizes on long timescales (herein ‘multidroplet size-conserved’ scenario’), depending on the scaffold to client ratio. Our simulations demonstrate that protein connectivity and condensate surface tension regulate the balance between these two scenarios. The multidroplet size-conserved scenario spontaneously arises at increasing surfactant-to-scaffold concentrations, when the interfacial penalty for creating small liquid droplets is sufficiently reduced by the surfactant proteins that are preferentially located at the interface. In contrast, low surfactant-to-scaffold concentrations enable continuous growth and fusion of droplets without restrictions. Overall, our work proposes one thermodynamic mechanism to help rationalize how size-conserved coexisting condensates can persist inside cells—shedding light on the roles of protein connectivity, binding affinity, and droplet composition in this process.
Funder: Junior Research Fellow at Kings College
Funder: Ernest Oppenheimer Memorial Trust; doi: http://dx.doi.org/10.13039/501100009978
Keywords: Article; /639/766/747; /631/57/2266; article